Randomized trial of 1‐week versus 2‐week intervals for endoscopic ligation in the treatment of patients with esophageal variceal bleeding. Issue 2 (17th May 2016) - Sheibani, Sarah; Khemichian, Saro; Kim, John J.; Hou, Linda; Yan, Arthur W.; Buxbaum, James; Dara, Lily; Laine, Loren
Abstract : The appropriate interval between ligation sessions for treatment of esophageal variceal bleeding is uncertain. The optimal interval would provide variceal eradication as rapidly as possible to lessen early rebleeding while minimizing ligation‐induced adverse events. We randomly assigned patients hospitalized with acute esophageal variceal bleeding who had successful ligation at presentation to repeat ligation at 1‐week or 2‐week intervals. Beta‐blocker therapy was also prescribed. Ligation was performed at the assigned interval until varices were eradicated and then at 3 and 9 months after eradication. The primary endpoint was the proportion of patients with variceal eradication at 4 weeks. Four‐week variceal eradication occurred more often in the 1‐week than in the 2‐week group: 37/45 (82%) versus 23/45 (51%); difference = 31%, 95% confidence interval 12%‐48%. Eradication occurred more rapidly in the 1‐week group (18.1 versus 30.8 days, difference = −12.7 days, 95% confidence interval −20.0 to −5.4 days). The mean number of endoscopies to achieve eradication or to the last endoscopy in those not achieving eradication was comparable in the 1‐week and 2‐week groups (2.3 versus 2.1), with the mean number of postponed ligation sessions 0.3 versus 0.1 (difference = 0.2, 95% confidence interval −0.02 to 0.4). Rebleeding at 4 weeks (4% versus 4%) and 8 weeks (11% versus 9%), dysphagia/odynophagia/chest pain (9% versus 2%), strictures (0% versus 0%), and mortality (7% versus 7%) were similar with 1‐week and 2‐week intervals. Conclusion: One‐week ligation intervals led to more rapid eradication than 2‐week intervals without an increase in complications or number of endoscopies and without a reduction in rebleeding or other clinical outcomes; the decision regarding ligation intervals may be individualized based on patient and physician preferences and local logistics and resources. (Hepatology 2016;64:549‐555)